Food assimilated by two sympatric populations of the brown planthopper Nilaparvata lugens (Delphacidae) feeding on different host plants contaminates insect DNA detected by RAPD-PCR analysis - Abdul Latif, M.; M. Y., Omar; Tan, Soon Guan, Prof. Dr.; Siti Shapor, Siraj, Prof. Dr.; Md Eaqub, Ali; Mohd Rafii, Yusop, Assoc. Prof. Dr. (FUNPEC-RP - Fundação de Pesquisas Científicas de Ribeirão Preto, 2013)
Link to publisher's homepage at www.funpecrp.com.br